Stator and rotor vent modelling in a MVA rated synchronous machine - Connor, Peter H.; Eastwick, Carol; Pickering, S.J.; Gerada, C.; Rolston, R. (2016)
An investigation into the solution dependence of a conjugate heat transfer computational fluid dynamics (CFD) model of a synchronous generator, with respect to meshing, has been carried out. Utilising CFD as a tool for investigating the airflow and thermal performance of electrical machines is increasing. Meshing is a vital part of the CFD process, but its importance is often misunderstood or overlooked in the context of electrical machine analyses; partly due to the relative mesh independency of the finite element analysis (FEA) numerical method. This paper demonstrates how a relatively complex, aircooled generator CFD model can be considerably influenced by changes in the mesh. Flow rate, velocity and windage effects are assessed as a function of the mesh adopted. Mesh changes have been shown to affect the mass flow rate through a single vent by up to 55% and the associated heat transfer coefficient by 128%.